Conceptual analysis of health systems resilience: A scoping review - Turenne, Charlotte Pailliard; Gautier, Lara; Degroote, Stéphanie; Guillard, Etienne; Chabrol, Fanny; Ridde, Valéry (Social science & medicine (1982), 2019)
System resilience has long been an area of study, and the term has become increasingly used across different sectors. Studies on resilience in health systems are more recent, multiplying particularly since the 2014 Ebola epidemic in West Africa. The World Health Organization (WHO) is calling for national governments to increase the resilience of their health systems. Concepts help define research objects and guide the analysis. Yet, to be useful, concepts need to be clear and precise. We aimed to improve the conceptual understanding of health systems resilience by conducting a scoping review to describe the state of knowledge in this area. We searched for literature in 10 databases, and analyzed data using a list of themes. We evaluated the clarity and the precision of the concept of health systems resilience using Daigneault & Jacob's three dimensions of a concept: term, sense, and referent. Of the 1091 documents initially identified, 45 met the inclusion criteria. Term: multiple terms are used, switching from one to the other to speak about the same subject. Sense: there is no consensus yet on a unique definition. Referent: the magnitude and nature of events that resilient health systems face differ with context, covering a broad range of situations from sudden crisis to everyday challenges. The lack of clarity in this conceptualization hinders the expansion of knowledge, the creation of reliable analytical tools, and the effectiveness of communication. The current conceptualization of health systems resilience is too scattered to enable the enhancement of this concept with great potential, opening a large avenue for future research. •In this paper, we provide a conceptual analysis of health systems resilience.•Based on the results of a scoping review, we argue that health systems resilience lacks conceptual maturity.•We call for clarification of the concept to guarantee effective communication and valid empirical study.